On-Farm Evaluation and System Productivity of Garden Pea-Boro-T. Aman Rice Cropping Pattern in Mymensingh (Bangladesh Agronomy Journal, 2020)
The experiment was conducted at Multi Location Testing site under On-Farm Research Division, Bangladesh Agricultural Research Institute, Mymensingh 2016- 17 and 2017-18 to evaluate the agro-economic performance of improved cropping pattern for increasing cropping intensity, system productivity and profitability as compared to farmers’ existing cropping pattern. The experiment was laid out randomized complete block design with six dispersed replications. Two cropping pattern viz., improved cropping pattern Garden pea (var. BARI Motorshuti-3) - Boro (var. BRRI dhan28) - T. Aman rice (var. BRRI dhan32) and farmers’ existing pattern Fallow - Boro (BRRI dhan28) - T. Aman rice (var. BRRI dhan32) as control were tested. Improved cropping pattern produced higher mean rice equivalent yield (30.26 t ha-1 yr.-1), production efficiency (74 kg ha-1 day-1 ), land utilization index (72 %) and labour employment (382 man-days ha-1 yr.-1) than farmers’ pattern which were 200, 37, 35 and 55% higher over existing pattern. Average gross return (Tk.486430 ha-1), gross margin (Tk. 284787 ha-1) and marginal benefit cost ratio (4.60) of improved pattern indicate it’s superiority over farmers’ pattern. The fertility status of soil i.e. pH, organic matter, total N, available P, S, Zn and B content in soil were increased over the initial soil due to addition of garden pea biomass. Thus, inclusion of garden pea in the existing pattern would improve soil health and system productivity as a whole. Experimental findings revealed that there is potential for greater adoption of intensified cropping systems with increased productivity and profitability as compared to rice–rice systems in Mymensingh region.Bangladesh Agron. J. 2020, 23(1): 37-46